Advances in Smart Cradle Design: Automation and Monitoring Systems for Infant Care - Avani Shinde; Prof. Beena Ballal; Mrunal Jagtap; Sanika Karade; Omkar Potare (International Journal of Advanced Control and System Engineering, 2024)
With the hectic schedules of working parents currently, raising a baby has become difficult. The arduous juggling between career obligations and childcare responsibilities can strain the very limits of human capacity. The choices have historically been to entrust the child's care to either senior family members or hiring a dedicated infant carer in situations like these, where time's unrelenting passage leaves little time for a full 24-hour commitment to the well-being of a priceless newborn. However, the innate anxieties of parental love persist, and doubts linger like shadows in the minds of these devoted guardians. Parents frequently request frequent, occasionally upsetting visits during valuable business breaks because they are constantly concerned about the safety and comfort of their cherished children. A smart cradle system offers a real-time resolution to this concern. It consists of a microphone and two sound sensors to identify the baby’s cries. When crying is detected, the system sends a message through the GSM module to the parent on the mobile phone. A wiper motor is used to swing the cradle. with a constant speed. In this project, we will use one dataset, that is, recordings of baby cries. The toy will move in response to the lower-frequency sobbing sound, while the mother's voice and other higher-frequency music will play. The temperature sensor automatically turns on the fan and alerts the parent to the ambient temperature close to the infant. The speed of the mini fan remains constant as it is not adjustable to different speed settings. The web application also includes reminders for scheduled vaccinations and medicines in an application.
Keywords: Internet of things (IoT); embedded systems; global system for mobile communications (GSM); sensor technology; wireless communication